Development and reliability of a quantitative personal hygiene assessment tool. - Delea, Maryann G.; Snyder, Jedidiah S.; Woreta, Mulat; Zewudie, Kassahun; Solomon, Anthony W.; Freeman, Matthew C. (International Journal of Hygiene & Environmental Health, 2020)
Personal hygiene practices, including facewashing and handwashing, reduce transmission of pathogens, but are difficult to measure. Using color theory principles, we developed and tested a novel metric that generates quantitative measures of facial and hand cleanliness, proxy indicators of personal hygiene practices. In this cross-sectional study, conventional qualitative cleanliness metrics (e.g., presence or absence of nasal and ocular discharge, dirt under nails or on finger pads and palms) were also recorded. We generated Gwet's agreement coefficients to determine the inter-rater reliability of novel and conventional metrics between various rating groups, where appropriate, including two non-blinded raters, non-blinded vs. blinded raters, three blinded raters, and blinded vs. computer raters. Inter-rater reliability of the novel metric was high across all rating groups, ranging from 0.98 (95% CI: 0.97, 0.99) to 0.90 (95% CI: 0.90, 0.91) for facial cleanliness, and 0.97 (95% CI: 0.96, 0.98) to 0.92 (95% CI: 0.91, 0.93) for hand cleanliness. Our novel metric generates more nuanced data than conventional qualitative metrics, and allows for quantifiable assessments of facial and hand cleanliness.